Evaluation of a Crowd Sourced Bathymetric Approach - Grinker, Barry; Solomon, Shaul; Hassin, Assif (The International Hydrographic Review, 2022)
Crowd-Sourced Bathymetry is the process of generating a harbor chart through collecting, enriching, processing, and aggregating depth (and other) measurements from a host of vessels, using standard navigation instruments, while engaged in routine maritime operations. This study explores the accuracy and limitations of one particular approach towards utilizing Crowd-Sourced data, comparing the results obtained from DockTech’s approach to that of a classic MBES survey. As DockTech is a for-profit startup that sells their product to various stakeholders in the maritime supply chain, a balance between protection of proprietary interest and scientific collaboration is necessary. As such, while specific details in regards to both chosen methodologies and their particular evaluations cannot be discussed, a general overview will be provided and the results of DockTech’s solution will be evaluated. This study is based on depth measurements collected by service vessels, active on a daily basis in Ashdod Port over the course of two months. Tug and Pilot boats use stand-alone GNSS navigation and navigation class Single Beam echo sounders for safety purposes when traversing the port and maneuvering between the wharfs. These depths, averaged over a relatively rough grid, were used to produce a chart of part of the port. Data from the service vessels did not include RTK GNSS navigation and hence ellipsoid referenced surveying techniques were not used in lieu of water level monitoring. This chart was then compared to another chart produced from a professional hydrographic survey of the port, using state of the art equipment and strict hydrographic control. The differences were then analyzed according to the latest edition of the IHO S-44 standards. Recommendations were suggested for some relatively simple measures which could enhance the accuracy achieved and the reliability of such a chart, at least for harbor maintenance purposes.